2012
DOI: 10.1210/jc.2011-1754
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Growth of Thyroid Carcinoma Cells, Suppresses Self-Renewal of Derived Cancer Stem Cells, and Potentiates the Effect of Chemotherapeutic Agents

Abstract: Metformin markedly diminished growth stimulation by insulin and showed an additive antimitogenic effect to chemotherapeutics agents. Therefore, our results suggest this drug as adjuvant treatment for thyroid cancer in type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 32 publications
12
137
0
4
Order By: Relevance
“…This finding is in good agreement with the results of an experimental study (14), in which an inhibitory effect of metformin on the growth of thyroid cells derived from nodular goiters was demonstrated. Metformin directly inhibits thyroid growth by activation of the AMPK/mammalian target of rapamycin (mTOR) pathway and antagonized the growth-stimulatory effect of insulin by inhibition of the MAPK pathway (14). Furthermore, in T2DM, metformin reduces insulin resistance and in turn hyperinsulinemia mainly by decreasing gluconeogenesis in the liver (24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in good agreement with the results of an experimental study (14), in which an inhibitory effect of metformin on the growth of thyroid cells derived from nodular goiters was demonstrated. Metformin directly inhibits thyroid growth by activation of the AMPK/mammalian target of rapamycin (mTOR) pathway and antagonized the growth-stimulatory effect of insulin by inhibition of the MAPK pathway (14). Furthermore, in T2DM, metformin reduces insulin resistance and in turn hyperinsulinemia mainly by decreasing gluconeogenesis in the liver (24).…”
Section: Discussionsupporting
confidence: 92%
“…However, that study (13) did not explicitly focus on T2DM and also did not consider antidiabetic drug intake. Focusing on the relationship between metformin and thyroid volume, a recent experimental study (14) demonstrated an inhibitory effect of metformin on the growth of human thyroid cells. Thus, it is intriguing to hypothesize that an association between T2DM and goiter, if existent, might be modulated by metformin use.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in vitro study, our study showed that metformin exerted a growthinhibitory effect on primary thyrocytes and thyroid cancer cells by reducing hyperinsulinemia and by a direct cellular action, including inhibition of cell cycle progression and induction of apoptosis (Chen et al 2012). Metformin markedly diminished growth stimulation by insulin on differentiated human thyroid cells, anaplastic thyroid carcinoma cells, a doxorubicin-resistant thyroid carcinoma cell line and thyroid cancer stem cells.…”
Section: Metformin and Thyroid Carcinomamentioning
confidence: 65%
“…Metformin was found to antagonize the growthstimulatory effect of insulin in vitro (Chen et al 2012). With addition of metformin, the insulin-induced increase of cell proliferation was almost abolished.…”
Section: Metformin and Ir In Thyroid Nodulesmentioning
confidence: 94%
“…in a serumfree medium, results in the formation of thyrospheres, although the size of the spheres is smaller than that of those generated in the presence of EGF and bFGF (Fig. 1) or in response to insulin and IGF1 and IGF2 stimulation (Malaguarnera et al 2011, Chen et al 2012. Spheres including thyrospheres are derived from a single stem cell that generates a self-copy of itself and differentiates into progenitor cells (Lan et al 2007, Deleyrolle & Reynolds 2009).…”
Section: Discussionmentioning
confidence: 99%